2012
DOI: 10.1111/jph.12046
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Manganese Increase Resistance of Clusterbean to Root Rot Caused by Rhizoctonia

Abstract: Clusterbean seedlings growing in soil inoculated with Rhizoctonia were treated with either 5 or 10 ppm Cu 2+ and Mn 2+ . Soil was inoculated by pretreatment with 250 mg (wet weight) of Rhizoctonia inoculum. A similar set of plants was maintained in uninoculated soil. Root rot incidence of plants treated with Cu 2+ 5 ppm, Cu 2+ 10 ppm, Mn 2+ 5 ppm and Mn 2+ 10 ppm was 26.6, 30.5, 11.8 and 29.2% less than the inoculated control, respectively. Inoculation with Rhizoctonia reduced chlorophyll, non-structural carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Brennan (1992) reported that the addition of manganese decreased the severity of 'wheat take-all' disease, but not the incidence. Similar results were reported by Heckman et al (2003), Simoglou and Dordas (2006), and Wadhwa et al (2013). The beneficial effects of copper and zinc application in controlling plant disease has been widely reported (Thongbai et al 1993a; Thongbai et al 1993b;Pernezny & Collins 1997;Khairulmazmi 2011;Stoltz & Wallenhammar 2012;Singh 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Brennan (1992) reported that the addition of manganese decreased the severity of 'wheat take-all' disease, but not the incidence. Similar results were reported by Heckman et al (2003), Simoglou and Dordas (2006), and Wadhwa et al (2013). The beneficial effects of copper and zinc application in controlling plant disease has been widely reported (Thongbai et al 1993a; Thongbai et al 1993b;Pernezny & Collins 1997;Khairulmazmi 2011;Stoltz & Wallenhammar 2012;Singh 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Reports showed that defense enzyme such as PAL and PPO, coupled with GST and GR, play different roles in regulating disease resistance 25 and pesticide degradation in plants 13 . Interestingly, research showed that Cu 27 , harpin 25 and melatonin 28 can strongly stimulate PAL and PPO activities in plants, whereas CHT can profoundly enhance GST and GR activities in plants 12 , 13 . Thus, the effects of CHT, CuCl 2 , harpin, and melatonin on PAL, PPO, GST, and GR activities in postharvest jujube fruit were investigated (Fig.…”
Section: Discussionmentioning
confidence: 99%